2016
DOI: 10.21522/tijcr.2014.03.01.art010
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice towards needle stick injury among health care workers in a tertiary Sudanese hospital

Abstract: Introduction: Percutaneous injuries, caused by needle sticks and other sharps, are a serious concern for all health care workers (HCWs) and pose a significant risk of occupational transmission of blood borne pathogen. Two million injuries are believed to occur each year among HCWs. Methodology: The study group consisted of 249 HCWs of various categories of a tertiary care hospital in Khartoum, Sudan. Data collection was carried out using a standardized questionnaire. To measure knowledge, attitude and practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
(21 reference statements)
2
6
1
Order By: Relevance
“…As reported by different studies, most of NSIs were reported by Nurses ( 8 , 9 , 32 ), and the majority of injuries happened in the patient room ( 28 , 32 ). In our study, intravenous (IV) cannula was the most common device involved in most incidents which are similar to what was reported by several studies.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…As reported by different studies, most of NSIs were reported by Nurses ( 8 , 9 , 32 ), and the majority of injuries happened in the patient room ( 28 , 32 ). In our study, intravenous (IV) cannula was the most common device involved in most incidents which are similar to what was reported by several studies.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, intravenous (IV) cannula was the most common device involved in most incidents which are similar to what was reported by several studies. ( 3 , 8 , 9 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many NSIs occur due to improper disposal of sharps e.g. unsuitable bins or on the floor and incorrect disposal of instruments by the dentists on instrumental trays (gichki, Islam and Murad, 2015). This is reflective of a lack of knowledge and awareness among dental practitioners.…”
Section: Resultsmentioning
confidence: 99%
“…Every healthcare facility ought to have an infection control application in place via a working sanatorium contamination control committee (olubuyide and olawuyi, 1995) This study has been conducted to assess the knowledge, attitude, and awareness of needle stick injury among dental practitioners. The main objectives of this study were, To investigate and evaluate the extent of attention, mindset, and practices regarding Needle Stick Injury, standard precautions and injection practice among dental practitioners, To study the factors resulting Needle Stick Injury and to assess hepatitis B immunization status among the practitioners (Dafaalla, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[5] and higher than the study conducted by Mohamed D. Dafaalla, Asgad suliman et al [3] were only 65.4% was fully vaccinated .Among the vaccinated candidates, 85.2% had not checked anti-HBs antibodies level; 5.9% have their anti HBsAb levels less than 10mlU/ml; 8.9% have their anti-HB s antibodies level above 10mlU/ml . 70.9% of the candidates always use gloves when they deal with needles in comparison to the study conducted by Mohamed D. Dafaalla, Asgad suliman, et al [3] in which only 63.6% always use gloves when they are dealing with needles 14.3% of the candidates had needle stick injury.Similar to the study conducted by Abadiga M et al [5]; which is quite low when compared to Ullah H et al [4] (64.9%) and Devaki T et al [2]; In which of the participants in that study had Needle prick injuries. The reason being, many students have participated in my study and they are in a comparatively less risk for needle prick injuries than health care workers like nurses.…”
Section: Specialtymentioning
confidence: 89%